ANALISIS PERAN PEREMPUAN YANG MASIH BERKARIR UNTUK MEMENUHI KEBUTUHAN KELUARGA DALAM PERSPEKTIF ISLAM - Muhammad Ramzhi Adhani (JURNAL SIPAKALEBBI, 2024)
The relationship between an older sibling in a family to meet the family’s economic needs from an Islamic perspective is a topic aimed at finding insights from Islamic teachings. This research was conducted using a descriptive method based on content from other studies. An individual’s knowledge and understanding highlight that the role of an older sibling is very important in the family, noting that there are various factors that cause a person to continue working for the family. This is despite the fact that a woman’s natural role is that of a mother, yet she still needs to work until today